Euro-Mediterranean partnership and youth policies in the MENA: why policy discourse travels but implementation doesn't. Issue 3 (27th May 2021) - Murphy, Emma; Sika, Nadine
ABSTRACT: This article explores the transfer of European approaches to youth policy to MENA regimes through their Mediterranean partnership programmes. Drawing on the papers and research conducted for the POWER2YOUTH (P2Y) research project, this conclusion investigates how European institutional and MENA governmental interests in similar models of youth policy-making converged but also why this convergence remained largely a feature of the discursive domain and did not translate into effective implementation or institutional embedding of policy in the authoritarian contexts of the MENA.